Strategi Transformasi Digital dan Keberlanjutan: Tinjauan Literatur Manajemen Strategik - Albertus Setyo Sumargo; Glenda Angeli; Achmad Solechan; Rina Diah Wahyuningsih; Anna Erlina Christianti (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study conducts a systematic literature review (SLR) to examine how digital transformation intersects with sustainability agendas at the corporate strategy level. The SLR follows evidence-informed management principles, including research question formulation, inclusion–exclusion criteria, systematic searching, and thematic synthesis. A total of 20 selected articles were analyzed and classified into five clusters: Digital Transformation (DT), Sustainability Strategy (SS), Digital–Sustainability Integration (INT), SLR Methodology (MET), and Strategic Theoretical Foundations (THEO). The review reveals a shift in the literature from parallel approaches toward strategic integration through the concept of twin transformation/twin transition, where digital and sustainability transformations should be designed and implemented simultaneously. Digital technologies (AI, IoT, big data, cloud, platforms) act as enablers of ESG performance, mainly through process efficiency, data transparency, green innovation, and ecosystem orchestration. However, DT does not automatically generate positive sustainability outcomes, as environmental trade-offs, rebound effects, and non-linear impacts may arise when digitalization is not aligned with ESG objectives. This study highlights the importance of aligning digital and sustainability strategies, strengthening ethical technology governance, developing dynamic capabilities, and designing digital-sustainable business models as a basis for sustainable competitive advantage. The findings also suggest future research agendas on measuring integration of digital transformation and business sustainability.